2018
DOI: 10.1186/s13058-018-0935-9
|View full text |Cite
|
Sign up to set email alerts
|

BRIP1 loss-of-function mutations confer high risk for familial ovarian cancer, but not familial breast cancer

Abstract: BackgroundGermline mutations in the BRIP1 gene have been described as conferring a moderate risk for ovarian cancer (OC), while the role of BRIP1 in breast cancer (BC) pathogenesis remains controversial.MethodsTo assess the role of deleterious BRIP1 germline mutations in BC/OC predisposition, 6341 well-characterized index patients with BC, 706 index patients with OC, and 2189 geographically matched female controls were screened for loss-of-function (LoF) mutations and potentially damaging missense variants. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 20 publications
(19 reference statements)
3
65
0
3
Order By: Relevance
“…4,5,28 However, it should be noted that recent studies have indicated that NBN is not significantly associated with HBOC, whereas BRIP1 has instead been associated with a significant risk for ovarian cancer but not breast cancer. 13,29 Our PV detection rate of 8.4% in these core genes is comparable to a previous report of the GC-HBOC. 5 These PVs we detected include two deleterious variants in BRCA1 that were previously missed by less comprehensive and sensitive screening methods.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…4,5,28 However, it should be noted that recent studies have indicated that NBN is not significantly associated with HBOC, whereas BRIP1 has instead been associated with a significant risk for ovarian cancer but not breast cancer. 13,29 Our PV detection rate of 8.4% in these core genes is comparable to a previous report of the GC-HBOC. 5 These PVs we detected include two deleterious variants in BRCA1 that were previously missed by less comprehensive and sensitive screening methods.…”
Section: Discussionsupporting
confidence: 89%
“…Most of the PVs (20/237; 8.4%) identified were found in genes that have a moderate to high risk for HBOC ( BRCA1, ATM, CHEK2, CDH1, PALB2, RAD51C and NBN ) according to the GC‐HBOC . However, it should be noted that recent studies have indicated that NBN is not significantly associated with HBOC, whereas BRIP1 has instead been associated with a significant risk for ovarian cancer but not breast cancer . Our PV detection rate of 8.4% in these core genes is comparable to a previous report of the GC‐HBOC .…”
Section: Discussionmentioning
confidence: 66%
“…We cannot exclude or verify this potential diagnosis clinically. BRIP1 has been shown to be a moderate‐risk ovarian cancer gene (Ramus et al., ; Weber‐Lassalle et al., ), most often caused by truncating variants (ClinVar). Two CRC patients with truncating BRIP1 variants and either familial CRC or polyposis have recently been reported (Martin‐Morales et al., ; Rosenthal et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, monoallelic PV/LPVs in the BRIP1 gene lead to a higher risk of OC that is estimated to be around 6% during a lifetime [127,132]. In contrast to the PALB2 gene, the risk of BC for BRIP1 PV/LPV carriers is estimated to be low or none [133][134][135], and there is insufficient evidence for risk management [54]. For the risk of OC, according to the NCCN guidelines, RRSO is an option that should be evaluated at 45-50 years or earlier based on family history [54].…”
Section: Palb2 Brip1 and Other Fanconi Anemia Genesmentioning
confidence: 99%